STEM on Demand – Can Current State of Higher Education Infrastructure Meet Expectations? - Jahic, Hatidza; Pilav-Velic, Amila (Naše gospodarstvo/Our economy, 2022)
One of the biggest challenges facing the education system in Bosnia and Herzegovina is bridging the gap between the current state of higher education and the demand for research, innovation and a robust STEM (Science, Technology, Engineering, Mathematics) curriculum. Higher education instiutions (HEIs) face poor R&D infrastructure while companies struggle with limited resources and the lack of internal researchers, all of which affect their capabilities to utilize university knowledge and research that will lead to further collaborations and innovations in STEM.Universities are primarily seen as a source of future employees as well as as a source of knowledge and innovation. This study aims to provide an overview and systematic analysis of the current state of scientific and research infrastructure and human resources in public and private universities located in the Sarajevo Canton region. This is done by using primary data collected through semi-structured interviews and a self-reporting comprehensive questionnaire in order to identify areas where further reforms and investments are needed. An analysis of the secondary data sources, such as current strategic documents and the existing assessments of education, was conducted. Consequently, this study offers several practical implications, including policy recommendations in areas such as higher education, research infrastructure and academic excellence, cooperation with the private sector, and IT infrastructure improvements.